INTEGRASI BUDAYA KEWIRAUSAHAAN KE DALAM PEMBELAJARAN MATA KULIAH RESTORAN - Widi Handayani, Titin Hera (Jurnal Cakrawala Pendidikan, 2016)
This research intended to conduct the integrated entrepreneurship culture <improve the subject of Restaurant, so that study can be more effective and qualified in the future< Peculiarly this research intended to find out the methods or learning strategic in integrating entrepreneurship and to know the result reached by students in integrating entrepreneurship study at management aspecL The subject of this research was students who taken the subject of Restaurant at Undergraduate Program of Food and Fashion Engineering Education< The object is integrated entrepreneurship culfurization with the subject of Restaurant at management aspecL Research procedure is conducted based on action research method which are planning, action, observation and reflection, treated in 6 cyc1es< The result of research indicates that the integration of entrepreneurship culture can improve the managerial competency of students at subject of RestauranL Gradually, the competency was increasing from first rotation to sixth, that is at non formal restaurant group, equal to 10 % with the average improvement of 2 %, formal restaurant group 27,5 % with the average improvement of 5,5 %, and cake & bakery group 10 % with the average improvement of 2 %< The result of action execution shows that the step of study consisted of (a) modules learning, (b) field visiting (c) business plan making, (d) implementation of business plan, (e) monitoring, reflecting and evaluating, which is applicable to improve the study quality<